PC composite material and preparation method and application thereof

By adding a specific proportion of hydrogenated petroleum resin to the PC material, the blocking membrane is formed, the problem of hydrolysis of PC materials under damp heat, and realizing the good water vapor resistance and size stability of the material, which is suitable for high -requirements applications.

CN119371799AActive Publication Date: 2025-01-28KINGFA SCI & TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411542806.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing PC materials are prone to hydrolysis under wet and heat conditions, resulting in surface micropore formation and imaging quality degradation, and the added layered filler leads to opaque appearance and poor dimensional stability.

Method used

Add a specific proportion of hydrogenated petroleum resin to PC materials, including C5 hydrogenated petroleum resin and C9 hydrogenated petroleum resin or DCPD hydrogenated petroleum resin, forming a blocking film to improve water vapor resistance, and optimize the material by controlling the addition and softening points to optimize the material Liquidity and chemical stability.

Benefits of technology

The good water vapor resistance, water vapor resistance and heat resistance of PC materials are realized, while maintaining the transparency and good size stability of the material. Applicable applications such as flat display monitors and radar hoods are suitable for high requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113155320000051
    Figure BDA0005113155320000051
  • Figure BDA0005113155320000061
    Figure BDA0005113155320000061
  • Figure BDA0005113155320000062
    Figure BDA0005113155320000062
Patent Text Reader

Abstract

The invention discloses a PC composite material and a preparation method and application thereof, and belongs to the technical field of high polymer materials. According to the invention, the hydrogenated petroleum resin with a specific addition amount is added into the PC, and the hydrogenated petroleum resin is limited to comprise the first hydrogenated petroleum resin and the second hydrogenated petroleum resin with a specific ratio, so that the two hydrogenated petroleum resins are utilized to synergistically improve the water vapor barrier property, the water vapor durability and the heat resistance of the material; the obtained material has good water vapor barrier property, water vapor durability and heat resistance, and is suitable for preparing a head-up display or a radome plastic part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a PC composite material and a preparation method and application thereof. Background Art

[0002] Polycarbonate (PC) is an amorphous, tasteless, odorless, non-toxic, transparent thermoplastic polymer with excellent impact toughness, transparency, dimensional stability, creep resistance, weather resistance, electrical insulation and other advantages. Since the PC main chain contains a large number of ester groups, it has high polarity, strong affinity with water, and high water vapor permeability. It is easy to hydrolyze under hot and humid conditions, and the molecular chain will break or produce small molecules, forming surface micropores or precipitation. When it is applied to HUD (head-up display) and radar cover, it affects the imaging clarity and quality of the camera. Therefore, it is of great significance to improve the water vapor barrier performance of PC and reduce the water vapor permeability. In addition, HUD and radar applications also require the parts to have good durability.

[0003] At present, the addition of layered fillers such as mica, montmorillonite, attapulgite, and organic clay increases the diffusion path and time of water molecules when diffusing in the layered channels arranged in a planar orientation, bypassing the sheets, which can improve the water vapor barrier properties. However, the appearance is poor and opaque, and due to interface bonding and contact surface problems, there are tiny defects inside the specimen and the dimensional stability is poor.

[0004] Therefore, it is necessary to develop a technology to enable transparent PC materials to have both good water vapor barrier properties and dimensional stability. Summary of the invention

[0005] Based on the defects of the prior art, the purpose of this application is to provide a PC composite material and its preparation method and application, aiming to make the PC composite material have good water vapor barrier and dimensional stability, transparent appearance and wide application range.

[0006] In order to achieve the above-mentioned purpose, in the first aspect, the present application provides a PC composite material, which comprises the following components in parts by weight: 100 parts of PC and 0.4 to 6 parts of hydrogenated petroleum resin, wherein the hydrogenated petroleum resin comprises a first hydrogenated petroleum resin and a second hydrogenated petroleum resin, the first hydrogenated petroleum resin is a C5 hydrogenated petroleum resin, the second hydrogenated petroleum resin is at least one of a C9 hydrogenated petroleum resin and a DCPD hydrogenated petroleum resin, and the weight ratio of the first hydrogenated petroleum resin to the second hydrogenated petroleum resin is 1:(1.25 to 2).

[0007] The water vapor permeation process of PC is that water molecules first adsorb on the PC surface, then attack the PC surface, and slowly penetrate into its structure, thereby reducing the hydrophilicity of the functional groups and changing the physical and chemical structure. A specific amount of hydrogenated petroleum resin is added to PC, and it is limited to contain a first hydrogenated petroleum resin and a second hydrogenated petroleum resin in a specific ratio. These two hydrogenated petroleum resins have good compatibility with PC and can combine with PC carbon chains through van der Waals forces to form a barrier film on the surface of the material, thereby improving the water vapor barrier property of the material. Moreover, their chemical stability and heat resistance are better than PC, and they can improve the water vapor durability and heat resistance of PC. Among them, the second hydrogenated petroleum resin has a significantly stronger effect on improving the water vapor barrier property, water vapor durability and heat resistance of PC. However, adding only the second hydrogenated petroleum resin will lead to deviation in the fluidity of the material, which is not conducive to processing and affects the performance of the second hydrogenated petroleum resin. The addition of the first hydrogenated petroleum resin will increase the fluidity of the material. Under the joint action of these two hydrogenated petroleum resins, the material can obtain better water vapor barrier property, water vapor durability and heat resistance.

[0008] The weight ratio of the first hydrogenated petroleum resin to the second hydrogenated petroleum resin is 1:(1.25-2), such as 1:1.25, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.

[0009] The amount of hydrogenated petroleum resin added will affect the water vapor barrier, water vapor durability and heat resistance of the material. If the amount is too little, the improvement effect of the water vapor barrier, water vapor durability and heat resistance of the material is not obvious; if the amount is too much, the hydrogenated petroleum resin is dispersed between the PC molecular chains, and the steric hindrance of the molecular chains is reduced, which is not conducive to the improvement of the water vapor barrier, water vapor durability and heat resistance of the material. Therefore, the application needs to control the amount of hydrogenated petroleum resin added to 0.4-6 parts by weight, such as 0.4 parts by weight, 0.5 parts by weight, 0.7 parts by weight, 0.9 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, 5 parts by weight, 5.5 parts by weight or 6 parts by weight. Preferably, the hydrogenated petroleum resin is 1.5-3.5 parts by weight to make the water vapor barrier, water vapor durability and heat resistance of the material better.

[0010] Preferably, the softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin are independently 80° C. to 150° C. More preferably, the softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin are independently 95° C. to 135° C.

[0011] When the softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin are controlled to be 80°C to 150°C, especially 95°C to 135°C, the chemical stability and heat resistance of the two are better, and the stratification of the material surface can be avoided, ensuring that the barrier layer formed on the material surface is more uniform and has better water vapor barrier properties. The softening point of the first hydrogenated petroleum resin can be selected to be 80°C, 85°C, 89°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, etc. The softening point of the second hydrogenated petroleum resin can be selected as 80°C, 85°C, 89°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, etc.

[0012] The softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin can be measured by the following method: GB / T 24138-2022 Petroleum resin.

[0013] Preferably, the PC has a melt flow rate of 10-30 g / 10 min at 300° C. and 1.2 kg.

[0014] Preferably, the PC is bisphenol A polycarbonate.

[0015] When the melt flow rate of the PC at 300°C and 1.2kg is within the range of 10-30g / 10min, the comprehensive performance of the material's water vapor barrier, water vapor durability and heat resistance is better. The melt flow rate of the PC at 300°C and 1.2kg can be selected as 10g / 10min, 12g / 10min, 14g / 10min, 16g / 10min, 18g / 10min, 20g / 10min, 22g / 10min, 24g / 10min, 26g / 10min, 28g / 10min or 30g / 10min, etc.

[0016] The melt flow rate of PC can be measured according to ISO 1133-2005.

[0017] Preferably, the PC composite material further comprises the following components in parts by weight: 0.01 to 2 parts of auxiliary agent.

[0018] Preferably, the auxiliary agent includes at least one of a flame retardant, an antioxidant, a filler, an antibacterial agent, and a toughening agent.

[0019] Exemplarily, the flame retardant includes at least one of a phosphorus flame retardant, a silicon flame retardant, a sulfur flame retardant and an inorganic flame retardant; the antioxidant includes at least one of a hindered phenol antioxidant (such as antioxidant 1076, antioxidant 1010, etc.), a phosphite antioxidant (such as antioxidant 168, etc.), and an aromatic amine antioxidant (such as antioxidant HP-136, etc.); the filler includes at least one of talc, mica, kaolin, barium sulfate, and wollastonite; the antibacterial agent includes at least one of a silver ion antibacterial agent and a vanillin antibacterial agent; the toughening agent includes at least one of a methyl methacrylate-butadiene-styrene ternary copolymer toughening agent MBS, a binary copolymer toughening agent of ethylene (E) and methyl acrylate (MA) EMA, an acrylonitrile-butadiene-styrene copolymer toughening agent SMA, an organosilicon toughening agent, and a core-shell structure acrylate copolymer toughening agent ACR.

[0020] Preferably, the weight percentage of PC in the PC composite material is above 92.6%, such as 92.6%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 99.6%.

[0021] In a second aspect, the present application also provides a method for preparing the PC composite material, comprising the following steps: mixing and dispersing all component raw materials, melt-extruding, and granulating to obtain the PC composite material.

[0022] Preferably, the temperature of the melt extrusion is 250-280°C.

[0023] In a third aspect, the present application also provides an application of the PC composite material in a head-up display or a radome plastic part, wherein the PC composite material can be used to prepare a housing of a head-up display.

[0024] Compared with the prior art, the beneficial effect of the present application is that: the present application adds a specific amount of hydrogenated petroleum resin to PC, and limits the hydrogenated petroleum resin to contain a first hydrogenated petroleum resin and a second hydrogenated petroleum resin in a specific ratio, so as to utilize the two hydrogenated petroleum resins to synergistically improve the water vapor barrier, water vapor durability and heat resistance of the material, so that the obtained material has good water vapor barrier, water vapor durability and heat resistance at the same time, and is suitable for preparing head-up display or radar cover plastic parts. DETAILED DESCRIPTION

[0025] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0026] The raw materials used in the following examples and comparative examples are shown in Table 1, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.

[0027] Table 1

[0028]

[0029] Each of the following examples and comparative examples provides a PC composite material, comprising the following steps: mixing and dispersing all the raw materials, feeding into a twin-screw extruder, melt extruding, and granulating to obtain a PC composite material, wherein the melt extrusion temperature is 250-280° C. The formulations of the PC composite materials of these examples and comparative examples are shown in Tables 2 and 3.

[0030] Table 2

[0031]

[0032] Table 3

[0033]

[0034] The following performance tests were performed on the PC composite materials of the above embodiments and comparative examples. The test results are shown in Table 4.

[0035] (1) Water vapor barrier performance test method

[0036] The PC composite particles were added into an injection molding machine, melted at 280°C in the first stage, 270°C in the second stage, 270°C in the third stage, 260°C in the fourth stage and 250°C in the fifth stage, and injection molded into 125 mm × 13.0 mm × 1 mm thick strips.

[0037] The instrument used is Illinois Instruments-7002 water vapor permeation analyzer, and the reference standards are GBT 21529-2008 Determination of water vapor transmission rate of plastic film and sheeting - Electrolytic sensor method, and ISO 15106-3: Plastics-Film and sheeting-Determinationof water vapour transmission rate-Part 3: Electrolytic detection sensor method. The test temperature is 38°C and the humidity is 90%.

[0038] (2) Dimensional stability

[0039] Add PC composite particles into the injection molding machine and melt them at 280℃ in the first stage, 270℃ in the second stage, 270℃ in the third stage, 260℃ in the fourth stage and 250℃ in the fifth stage to prepare a 100mm*100mm*2mm sample and record the length as L 0 , bake at 80℃ for 24 hours, test the length of the sample after baking and record it as L 1 , dimensional change rate = (L 1 -L 0 ) / L 0 *100%.

[0040] (3) Durability test

[0041] The PC composite particles are added into an injection molding machine, melted at a temperature of 270°C to 290°C, and injection molded into a standard color plate with a length*width*thickness of 54mm*84mm*2mm. The haze is measured and then placed in a PCT pressure cooker cooking tester for testing at 0.17MPa, 120°C, saturated humidity (100%RH), and a test time of 1000 hours. The haze is then measured and the haze change rate is calculated. The haze test is measured using a transmittance / haze meter WGT-S from Shanghai Jingke.

[0042] Table 4

[0043]

[0044]

[0045] From the above data, it can be seen that the PC composite materials of each embodiment have good water vapor barrier properties, water vapor durability and heat resistance. For example, the water vapor barrier property is 0.5g / (m 2*day), the dimensional change rate after baking at 80℃ for 24 hours is less than 1.2%, and the haze change rate after being placed at 0.17MPa, 120℃ and 100%RH for 1000h is less than 15%.

[0046] In Comparative Example 1, only C5 hydrogenated petroleum resin was added, and C9 hydrogenated petroleum resin and DCPD hydrogenated petroleum resin were not added. The water vapor barrier property, water vapor durability and heat resistance of the material were all deviated.

[0047] In Comparative Examples 2 to 3, only DCPD hydrogenated petroleum resin or C9 hydrogenated petroleum resin was added, but C5 hydrogenated petroleum resin was not added. The processing performance of the material was deviated, and the water vapor barrier property, water vapor durability and heat resistance were also deviated.

[0048] In Comparative Examples 4 to 5, silicone oil or white oil is added. Silicone oil and white oil have poor compatibility with PC and are easily precipitated, resulting in an unstable surface barrier layer and poor performance, which causes deviations in the water vapor barrier property, water vapor durability and other properties of the material.

[0049] From the comparison of Examples 1 to 4, it can be seen that the amount of hydrogenated petroleum resin added will affect the water vapor barrier, water vapor durability and heat resistance of the material. In order to make the water vapor barrier, water vapor durability and heat resistance of the material better, it is preferred that when the amount of PC is 100 parts by weight, the amount of hydrogenated petroleum resin added is 1.5 to 3.5 parts by weight.

[0050] Comparison of Examples 3 and 7 to 10 shows that the softening point of the first hydrogenated petroleum resin affects the water vapor barrier, water vapor durability and heat resistance of the material. Preferably, the softening point is 95°C to 135°C to make the obtained material have better comprehensive performance in water vapor barrier, water vapor durability and heat resistance.

[0051] From the comparison of Examples 3 and 11 to 14, it can be seen that the softening point of the second hydrogenated petroleum resin will affect the water vapor barrier, water vapor durability and heat resistance of the material. The softening point is preferably 95°C to 135°C so that the comprehensive performance of water vapor barrier, water vapor durability and heat resistance of the obtained material is better.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A PC composite material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of PC and 0.4 to 6 parts of hydrogenated petroleum resin, wherein the hydrogenated petroleum resin comprises a first hydrogenated petroleum resin and a second hydrogenated petroleum resin, the first hydrogenated petroleum resin is a C5 hydrogenated petroleum resin, the second hydrogenated petroleum resin is at least one of a C9 hydrogenated petroleum resin and a DCPD hydrogenated petroleum resin, and the weight ratio of the first hydrogenated petroleum resin to the second hydrogenated petroleum resin is 1:(1.25 to 2).

2. The PC composite material according to claim 1, characterized in that The hydrogenated petroleum resin is 1.5 to 3.5 parts.

3. The PC composite material according to claim 1, characterized in that The softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin are independently 80° C. to 150° C.

4. The PC composite material according to claim 3, characterized in that: The softening points of the first hydrogenated petroleum resin and the second hydrogenated petroleum resin are independently 95° C. to 135° C.

5. The PC composite material according to claim 1, characterized in that: The PC has a melt flow rate of 10-30 g / 10 min at 300° C. and 1.2 kg.

6. The PC composite material according to claim 1, characterized in that: The invention also comprises the following components in parts by weight: 0.01 to 2 parts of auxiliary agent.

7. The PC composite material according to claim 6, characterized in that The auxiliary agent includes at least one of a flame retardant, an antioxidant, a filler, an antibacterial agent, and a toughening agent.

8. A method for preparing a PC composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing and dispersing all component raw materials, melting and extruding, and granulating to obtain a PC composite material.

9. The method for preparing the PC composite material according to claim 8, characterized in that: The temperature of the melt extrusion is 250-280°C.

10. Use of the PC composite material according to any one of claims 1 to 7 in a head-up display or a radome plastic part.

Citation Information

Patent Citations

  • Chemical solvent-resistant conduction type PC / ABS composite material

    CN109265954A

  • Resin composition and molded article

    CN111748190A

  • Hydrolysis-resistant PC resin composition and preparation method thereof

    CN115850935A

  • PC / ABS modified material and preparation method thereof

    CN117304640A

  • Polypropylene composition and preparation method thereof

    CN117757185A